The Influence of Knowledge, Social Media, and Investment Motivation on Investment Interest among the Millennial Generation in Palopo City - Ramadhan, Anugrah Riskullah; Jasman, Jumawan; Sahrir, Sahrir (Journal of Applied Business, Taxation and Economics Research, 2026)
This research aim to explore the influence of investment knowledge, social media, And investment motivation to investment interest. With identify connection between third variables This expected can be found outlook new Which useful in designing program management finance Which more effective. This research method uses quantitative data with primary data sources and a sample of 100 respondents. The data was obtained from response respondents on statement in questionnaire And analyzed use analysis multiple linear regression. The results of this study indicate that investment knowledge has an effect positive and significant on investment interest, social media has an influence positive and significant on investment interest, and investment motivation has a positive and significant effect on investment interest.